Modeling and stability of grid-connected power converters with virtual inertia control - Yang, Haoxin (Nanyang Technological University, 2020)
Due to the ever-increasing power demands and a desire for carbon footprint reduction, conventional fossil fuel-based energy generations are gradually replaced by renewable energy sources (RESs), e.g., wind power and solar photovoltaics. However, the lack of inertia contributions from RESs, which are essentially power electronic converters in replacement of synchronous generators, will challenge the frequency control and stability. To resolve this problem, the disturbed virtual inertia provided by grid-connected power converters is attracting growing attention due to its effectiveness and simplicity. However, although being practical for system inertia improvement, the grid-connected power converters with virtual inertia control also bring instability concerns. Therefore, this thesis mainly focuses on the analysis about the modeling as well as the stability of grid-connected power converters with virtual inertia control. First of all, this thesis focuses on the system performance and stability under islanding operation modes. Specifically, unlike synchronous inertia, frequency measurements and DC-link voltage regulations are necessitated for virtual inertia implementations. As a consequence, the delay effects brought by these dynamics might cause instability concerns. Two different cases are studied in this part: one is the moving average filter-based virtual inertia control and the other one is the centralized virtual inertia control. To fill the research gap, this thesis presents a detailed analysis of the effects of delay on the frequency regulation system. With loop gains and Bode diagrams, it is revealed that the system loop gain shows a negative relationship between the inertia ratio and stability margins, indicating that a high virtual inertia level can bring instability issues into a single area power system. To tackle this instability issue, this paper proposes a modified virtual inertia control to mitigate the phase lag and improve system stability. For verification, the experimental results are presented, which are consistent with the theoretical analysis. This thesis also investigates the modeling and stability of power converters with virtual inertia control in the grid-connected modes. To fully pinpointing the grid-converter interactions, exploring the sources of resonances, and verifying the mirror frequency coupling effects, the sequence impedance models are introduced and adopted in this part. As the basic block for the inertia emulation, the sequence impedance expressions of a DC-link voltage-controlled converter are analyzed and derived firstly. It is found that the system would generate more mirror-frequency components in the rectifier mode, while more the same frequency components in the inverter mode. Next, as shown in Chapter 4, the system impedance magnitudes decrease greatly as the virtual inertia gain increases, indicating that the grid-connected power converter would become extensively sensitive to grid voltage perturbations. As a verification, the simulation results show that the virtual inertia control would totally distort the output currents due to the impedance reductions. Additionally, in the presence of the grid impedance, the system stability is evaluated with the impedance-based stability criterion. It is found out that the system closed-loop poles would drift to the right-half-plane as virtual inertia gain increases. Simulation results are also provided, which are consistent with the theoretical analysis. Overall, this thesis mainly focuses on the modeling and stability of grid-connected power converters with virtual inertia control, whether in islanding modes or grid-connected modes. Both system-level and converter-level stabilities are discussed. As the renewable integration trend continues, new challenges and opportunities will be introduced by the virtual inertia control. For future works, the impacts of mirror-frequency impedance matrixes on the system stability and the design of advanced virtual inertia controllers are worthy of further investigations.